Creep-resistant titanium alloys
A titanium alloy with tailored compositions and heat treatments forms intermetallic precipitates, enhancing creep resistance and tensile strength for high-temperature applications.
Patent Information
- Application Number
- JP2021510155
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-08-28
- Filing Date
- 2019-06-17
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2039-06-17
AI Technical Summary
Conventional titanium alloys exhibit limited creep resistance at elevated temperatures, which restricts their use in high-temperature applications.
A titanium alloy composition comprising specific weight percentages of aluminum, tin, molybdenum, zirconium, silicon, and germanium, along with suitable heat treatments, forms intermetallic precipitates that enhance creep resistance.
The alloy demonstrates improved creep resistance at elevated temperatures, with reduced steady-state creep rates and increased tensile strength, making it suitable for high-temperature applications.
Smart Images

Figure 0007605733000003 
Figure 0007605733000004 
Figure 0007605733000005
Abstract
Description
[Technical field]
[0001]
[0001] This disclosure relates to creep resistant titanium alloys. [Background technology]
[0002] Titanium alloys typically exhibit high strength-to-weight ratios, are corrosion resistant, and are creep resistant at moderately elevated temperatures. For example, Ti-5Al-4Mo-4Cr-2Sn-2Zr alloy (also designated "Ti-17 alloy" having a composition specified by UNS R58650) is a commercially available alloy widely used in jet engine applications requiring a combination of high strength, fatigue resistance, and toughness at operating temperatures up to 426.7°C (800°F). Other examples of titanium alloys used in high temperature applications include Ti-6Al-2Sn-4Zr-2Mo alloy (also designated "Beta-C" having a composition specified by UNS R54620) and Ti-3Al-8V-6Cr-4Mo-4Zr alloy (also designated "Beta-C" having a composition specified by UNS R58640). However, these alloys have limited creep resistance at elevated temperatures. Therefore, there has been a need for titanium alloys with improved creep resistance at elevated temperatures. Summary of the Invention
[0003]
[0003] According to one non-limiting embodiment of the present disclosure, the titanium alloy comprises, in weight percent based on total alloy weight, 5.5-6.5 aluminum, 1.5-2.5 tin, 1.3-2.3 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.1-2.0 germanium, titanium, and impurities.
[0004]
[0004] According to another non-limiting aspect of the present disclosure, the titanium alloy consists essentially of, in weight percent based on total alloy weight, 5.5-6.5 aluminum, 1.5-2.5 tin, 1.3-2.3 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.1-2.0 germanium, titanium, and impurities.
[0005]
[0005] According to another non-limiting aspect of the present disclosure, the titanium alloy contains, in weight percent based on the total alloy weight, 2-7 aluminum, 0-5 tin, 0-5 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.05-2.0 germanium, 0-0.30 oxygen, 0-0.30 iron, 0-0.05 nitrogen, 0-0.05 carbon, 0-0.015 hydrogen, titanium, and impurities.
[0006]
[0006] The features and advantages of the alloys, articles, and methods described herein can be better understood by reference to the accompanying drawings. [Brief description of the drawings]
[0007] [Figure 1] 1 is a graph plotting creep strain over time for certain non-limiting embodiments of the titanium alloys of the present disclosure compared to certain conventional titanium alloys. [Diagram 2]
[0008] 1 is a photomicrograph of a non-limiting embodiment of a titanium alloy of the present disclosure and a graph showing the results of an energy dispersive X-ray (XRD) scan of the alloy before and after sustained loading. [Diagram 3]
[0009] 3 is a photomicrograph of the titanium alloy of FIG. 2 and a graph showing the results of an XRD scan of the alloy and partitioning of Zr / Si / Ge into intermetallic precipitates after the alloy was heated at 482.2° C. (900° F.) for 125 hours under a sustained load of 358.5 MPa (52 ksi). [Figure 4]
[0010] FIG. 4 is an elemental map of the titanium alloy of FIG. 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008]
[0011] The reader will appreciate the foregoing details, and others as well, in light of the following detailed description of certain non-limiting embodiments of the present disclosure.
[0012] In describing the present invention in non-limiting embodiments, except in the operating examples or where otherwise noted, all numbers indicating quantities or characteristics should be understood in all cases to be modified by the term "about". Thus, unless specifically stated to the contrary, any numerical parameters set forth in the following description are approximations that may vary depending on the desired properties sought in the materials and methods of the present disclosure. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be construed by applying ordinary rounding techniques in light of the number of reported significant digits. All ranges set forth herein are inclusive of the stated endpoints unless otherwise indicated.
[0009]
[0013] Any patent, literature, or other disclosure material that is stated to be incorporated herein by reference in whole or in part is incorporated herein only to the extent that the incorporated material does not contradict existing definitions, descriptions, or other disclosure material set forth in this disclosure. Thus, to the extent necessary, the disclosure set forth herein takes precedence over any conflicting material incorporated herein by reference. Any material or portion thereof that is stated to be incorporated herein by reference but that contradicts existing definitions, descriptions, or other disclosure material set forth herein is incorporated only to the extent that no conflict occurs between the incorporated material and the existing disclosure material.
[0010]
[0014] As used herein, a titanium alloy "comprising" a particular composition is intended to include alloys "consisting essentially of" or "consisting of" the indicated composition. It is understood that titanium alloy compositions "comprising," "consisting of," or "consisting essentially of" a particular composition described herein may also include impurities.
[0011]
[0015] Articles and components in high temperature environments may undergo creep. As used herein, "high temperature" refers to temperatures above about 200°F. Creep is a time-dependent strain that occurs under stress. Creep that occurs at reduced strain rates is referred to as primary creep, creep that occurs at minimal, nearly constant strain rates is referred to as secondary (steady-state) creep, and creep that occurs at accelerated strain rates is referred to as tertiary creep. Creep strength is the stress that produces a given creep strain in a creep test at a given time in a specific, constant environment.
[0012]
[0016] The creep resistance behavior of titanium and titanium alloys at elevated temperatures and under sustained loads depends primarily on the microstructural characteristics. Titanium has two allotropes: the beta ("β") phase, which has a body-centered cubic ("bcc") crystal structure, and the alpha ("α") phase, which has a hexagonal close-packed ("hcp") crystal structure. In general, beta titanium alloys exhibit poor elevated temperature creep strength. The poor elevated temperature creep strength is a result of the significant concentration of beta phase that these alloys exhibit at elevated temperatures, such as, for example, 482.2°C (900°F). The beta phase, due to its body-centered cubic structure, is less resistant to creep and leads to many deformation mechanisms. These shortcomings have limited the use of beta titanium alloys.
[0013]
[0017] One group of titanium alloys that is widely used in a variety of applications are α / β titanium alloys. In α / β titanium alloys, the distribution and size of the primary α particles can directly affect creep resistance. Various published reviews of studies of α / β titanium alloys containing silicon have shown that precipitation of silicides at grain boundaries can further improve creep resistance, but at the expense of loss of room temperature tensile ductility. The decrease in room temperature tensile ductility that occurs with silicon addition typically limits the silicon concentration that can be added to 0.3% (by weight).
[0014]
[0018] The present disclosure is directed, in part, to alloys that address certain limitations of conventional titanium alloys. One embodiment of the disclosed titanium alloy includes (i.e., comprises), in weight percent based on total alloy weight, 5.5-6.5 aluminum, 1.5-2.5 tin, 1.3-2.3 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.1-2.0 germanium, titanium, and impurities. Another embodiment of the disclosed titanium alloy includes, in weight percent based on total alloy weight, 5.5-6.5 aluminum, 1.7-2.1 tin, 1.7-2.1 molybdenum, 3.4-4.4 zirconium, 0.03-0.11 silicon, 0.1-0.4 germanium, titanium, and impurities. Yet another embodiment of the disclosed titanium alloy includes, in weight percent based on total alloy weight, 5.9-6.0 aluminum, 1.9-2.0 tin, 1.8-1.9 molybdenum, 3.7-4.0 zirconium, 0.06-0.11 silicon, 0.1-0.4 germanium, titanium, and impurities. In a non-limiting embodiment of the disclosed alloy, the incidental elements and other impurities in the alloy composition can include or consist essentially of one or more of oxygen, iron, nitrogen, carbon, hydrogen, niobium, tungsten, vanadium, tantalum, manganese, nickel, hafnium, gallium, antimony, cobalt, and copper. Certain non-limiting embodiments of the titanium alloys of the present disclosure can include, in weight percent based on total alloy weight, 0.01-0.25 oxygen, 0-0.30 iron, 0.001-0.05 nitrogen, 0.001-0.05 carbon, 0-0.015 hydrogen, and 0 to 0.1 each of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper.
[0015]
[0019] Aluminum can be included in the alloys of the present disclosure to increase the alpha content and improve strength. In certain non-limiting embodiments of the present disclosure, aluminum can be present in a weight concentration of 2-7% based on the total alloy weight. In certain non-limiting embodiments, aluminum can be present in a weight concentration of 5.5-6.5%, or in some embodiments, 5.9-6.0%, based on the total alloy weight.
[0016]
[0020] Tin can be included in the alloys of the present disclosure to increase the alpha content and improve strength. In certain non-limiting embodiments of the present disclosure, tin can be present in a weight concentration of 0-4% based on the total alloy weight. In certain non-limiting embodiments, tin can be present in a weight concentration of 1.5-2.5%, or in some embodiments, 1.7-2.1%, based on the total alloy weight.
[0017]
[0021] Molybdenum can be included in the alloys of the present disclosure to increase the beta content and improve strength. In certain non-limiting embodiments of the present disclosure, molybdenum can be present in a weight concentration of 0-5% based on the total alloy weight. In certain non-limiting embodiments, molybdenum can be present in a weight concentration of 1.3-2.3%, or in some embodiments, 1.7-2.1%, based on the total alloy weight.
[0018]
[0022] Zirconium can be included in the alloys of the present disclosure to increase the alpha content, increase strength, and increase creep resistance by forming intermetallic precipitates. In certain non-limiting embodiments of the present disclosure, zirconium can be present in a weight concentration of 1-10% based on the total alloy weight. In certain non-limiting embodiments, zirconium can be present in a weight concentration of 3.4-4.4%, or in some embodiments, 3.5-4.3%, based on the total alloy weight.
[0019]
[0023] Silicon can be included in the alloys of the present disclosure to form intermetallic precipitates to enhance creep resistance. In certain non-limiting embodiments of the present disclosure, silicon can be present in a weight concentration of 0.01 to 0.30% based on the total alloy weight. In certain non-limiting embodiments, silicon can be present in a weight concentration of 0.03 to 0.11%, or in some embodiments, 0.06 to 0.11%, based on the total alloy weight.
[0020]
[0024] Germanium may be included in the titanium alloy embodiments of the present disclosure to improve secondary creep rate behavior at elevated temperatures. In certain non-limiting embodiments of the present disclosure, germanium may be present at a weight concentration of 0.05-2.0% based on the total alloy weight. In certain non-limiting embodiments, germanium may be present at a weight concentration of 0.1-2.0%, or in some embodiments, 0.1-0.4%, based on the total alloy weight. Without intending to be bound by any theory, it is believed that the germanium content of the alloy, in conjunction with a suitable heat treatment, may promote the precipitation of zirconium-silicon-germanium intermetallic compound precipitates. The germanium addition may be, for example, from a pure metal, or from a master alloy of germanium and one or more other suitable metallic elements. Si-Ge and Al-Ge may be suitable examples of master alloys. Certain master alloys may be in the form of powder, pellets, wire, crushed chips, or sheets. The titanium alloys described herein are not limited in this respect. After final melting to obtain a substantially homogeneous mixture of titanium and alloying elements, the cast ingot can be thermomechanically processed by one or more steps of forging, rolling, extruding, drawing, swaging, upsetting, and annealing to obtain the desired microstructure. It should be understood that the alloys of the present disclosure may be thermomechanically processed and / or treated by other suitable methods.
[0021]
[0025] Non-limiting embodiments of the methods of making the disclosed titanium alloys include annealing, solution treating, and heat treating by a combination of annealing, solution ageing (STA), direct aging, or thermal cycling to obtain a desired balance of mechanical properties. As used herein, the "solution ageing (STA)" method refers to a heat treatment method applied to a titanium alloy that includes solution treating the titanium alloy at a solution treatment temperature below the beta transus temperature of the titanium alloy. In non-limiting embodiments, the solution treatment temperature is in the temperature range of about 971.1°C (1780°F) to about 982.2°C (1800°F). The solution treated alloy is subsequently aged by heating the alloy for a period of time to an aging temperature range that is below the beta transus temperature of the titanium alloy and below the solution treatment temperature. As used herein, the terms "heated to" or "heating to" and the like refer to a temperature, temperature range, or minimum temperature, and mean that the alloy is heated until at least a desired portion of the alloy has a temperature at least equal to a reference temperature or minimum temperature, or within a reference temperature range, throughout the range of the portion. In a non-limiting embodiment, the solution treatment time ranges from about 30 minutes to about 4 hours. It is recognized that in some non-limiting embodiments, the solution treatment time may be less than 30 minutes or greater than 4 hours, and generally depends on the size and cross-section of the titanium alloy. Once the solution treatment is complete, the titanium alloy is cooled to ambient temperature at a rate that depends on the cross-sectional thickness of the titanium alloy.
[0022]
[0026] The solution treated titanium alloy is subsequently aged at an aging temperature, also referred to herein as the "age hardening temperature", which is in the α+β two-phase field and below the β transus temperature of the titanium alloy. In a non-limiting embodiment, the aging temperature is in the temperature range of about 579.44°C (1075°F) to about 607.2°C (1125°F). In some non-limiting embodiments, the aging time can be in the range of about 30 minutes to about 8 hours. It is recognized that in some non-limiting embodiments, the aging time may be less than 30 minutes or more than 8 hours, and generally depends on the size and cross-section of the titanium alloy product form. The general techniques used in STA processing of titanium alloys are known to those skilled in the art and therefore will not be described further herein.
[0023]
[0027] Although it is recognized that the mechanical properties of titanium alloys are generally affected by the size of the specimen being tested, in certain non-limiting embodiments of the titanium alloys of the present disclosure, the titanium alloy has a mechanical property of at least 8×10 tensile strength under a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7° C. (890° F.). -4 (24 hours) -1 Also, for example, certain non-limiting embodiments of the titanium alloys disclosed herein exhibit a steady-state (also known as second order or "stage II") creep rate of less than 8×10 at a temperature of 482.2° C. (900° F.) and a load of 358.5 MPa (52 ksi). -4 (24 hours) -1 In certain non-limiting embodiments of the present disclosure, the titanium alloy exhibits an ultimate tensile strength of at least 130 ksi at 900°F. In other non-limiting embodiments, the titanium alloy of the present disclosure exhibits a time to 0.1% creep strain of less than 20 hours at 900°F under a load of 52 ksi.
[0024]
[0028] The following examples are intended to further illustrate non-limiting embodiments of the present disclosure without limiting the scope of the invention. Those of skill in the art will recognize that variations of the following examples are possible within the scope of the invention, which is defined solely by the claims. EXAMPLES
[0025] Example 1
[0029] Table 1 lists the elemental compositions of certain non-limiting embodiments of titanium alloys of the present disclosure ("Experimental Titanium Alloy No. 1," "Experimental Titanium Alloy No. 2," and "Experimental Titanium Alloy No. 3") along with a comparative titanium alloy that does not contain any intentional addition of germanium ("Comparative Titanium Alloy").
[0026] [Table 1]
[0027]
[0030] A plasma arc furnace was used to plasma arc melt (PAM) heat the comparative titanium alloy, experimental titanium alloy #1, experimental titanium alloy #2, and experimental titanium alloy #3 listed in Table 1 to produce 9 inch diameter rods weighing approximately 400 lb to 800 lb, respectively. The rods were remelted in a vacuum arc remelting (VAR) furnace to produce 10 inch diameter ingots. Each ingot was converted into a 3 inch diameter billet using a hot working press. After beta forging to 7 inches (17.78 cm) diameter, alpha + beta prestrain forging to 5 inches (12.70 cm) diameter, and beta finish forging to 3 inches (7.62 cm) diameter, the ends of each billet were trimmed to remove suck-ins and end cracks, and the billets were cut into multiple pieces. At 7 inches (17.78 cm) diameter, the top and bottom of each billet were sampled for chemistry and beta transus. Based on the chemistry results of the middle billets, 2 inch (5.08 cm) long samples were cut from the billets and "pancake" forged in a press. The pancake specimens were heat treated under solution and aging conditions as follows: the titanium alloy was solution treated at 1780°F to 1800°F for 4 hours, the titanium alloy was cooled to ambient temperature at a rate dependent on the section thickness of the titanium alloy, the titanium alloy was aged at 1025°F to 1125°F for 8 hours, and the titanium alloy was air cooled.
[0028]
[0031] Control specimens for room temperature and elevated temperature tensile tests, creep tests, fracture toughness, and microstructural analysis were cut from the STA processed pancake specimens. Final chemical analysis was performed on the fracture toughness specimens after testing to ensure accurate correlation between chemistry and mechanical properties. Certain mechanical properties of the experimental titanium alloys listed in Table 1 were measured and compared to those of the comparative titanium alloys listed in Table 1. The results are listed in Table 2. Tensile tests were performed according to American Society for Testing and Materials (ASTM) standard E8 / E8M-09 ("Standard Test Methods for Tension Testing of Metallic Materials", ASTM International, 2009). As shown by the results listed in Table 2, the experimental titanium alloy specimens exhibited ultimate tensile strength and yield strength at room temperature comparable to the comparative titanium alloys without the intentional addition of germanium.
[0029] [Table 2]
[0030]
[0032] Creep-rupture testing according to ASTM E139 was performed on the alloys listed in Table 1. The results are shown in FIG. 1. The experimental titanium alloys of the present disclosure exhibited highly favorable secondary creep rates compared to the comparative titanium alloys. With reference to FIGS. 2-4, precipitation of zirconium-silicon-germanium intermetallic phases was detected in experimental titanium alloy No. 2 after being subjected to creep under sustained load and elevated temperature beyond the time for primary (or stage I) creep. As shown in FIG. 1, the experimental titanium alloy specimen of the present disclosure exhibited steady-state creep after approximately 30 hours at 482.2°C (900°F) and 358.5 MPa (52 ksi). The comparative titanium alloy exhibited a time to 0.1% creep strain of 19.4 hours at 482.2°C (900°F) and 358.5 MPa (52 ksi). Experimental Titanium Alloy #1, Experimental Titanium Alloy #2, and Experimental Titanium Alloy #3 all exhibited significantly longer times to 0.1% creep strain under a load of 358.5 MPa (52 ksi) at 482.2°C (900°F): 32.6 hours, 55.3 hours, and 93.3 hours, respectively.
[0031]
[0033] Samples tested prior to creep (but after heat treatment) did not reveal the presence of intermetallic precipitates. Referring to FIG. 2, an energy dispersive X-ray (EDS) elemental scan of experimental titanium alloy No. 2 prior to creep showed a substantially uniform distribution of germanium in the α / β microstructure without intermetallic particles. In FIGS. 3-4, partitioning of zirconium, silicon, and germanium into the intermetallic particles is seen after creep. The intermetallic particles generally show aluminum depletion compared to the surrounding alpha particles. The precipitation of intermetallic particles after creep was particularly unexpected and surprising. Without intending to be bound by any theory, it is believed that the intermetallic particles may improve the secondary creep of the alloy without substantially affecting the high temperature yield strength.
[0032]
[0034] There are many potential uses for the alloys of the present disclosure. As described and demonstrated above, the titanium alloys described herein are advantageously used in a variety of applications where creep resistance at elevated temperatures is important. Articles of manufacture for which the titanium alloys of the present disclosure may be particularly advantageous include certain aerospace and aviation applications, such as jet engine turbine disks and turbofan blades. Those skilled in the art will be able to manufacture the aforementioned devices, components, and other articles of manufacture from the alloys of the present disclosure without the need for further description herein. The foregoing examples of possible applications of the alloys of the present disclosure are presented by way of example only and are not intended to be exhaustive of all applications to which the alloy product forms of the present invention may be applied. Those skilled in the art will be able to readily identify additional applications for the alloys described herein upon reading this disclosure.
[0033]
[0035] Various non-exhaustive, non-limiting embodiments of the novel alloys and methods of the present disclosure may be useful alone or in combination with one or more other embodiments described herein. Without limiting the foregoing, in a first, non-limiting embodiment of the present disclosure, the titanium alloy includes, in weight percent based on the total alloy weight, 5.5-6.5 aluminum, 1.5-2.5 tin, 1.3-2.3 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.1-2.0 germanium, titanium, and impurities.
[0034]
[0036] According to a second non-limiting aspect of the present disclosure, which can be used in combination with the first aspect, the titanium alloy includes, in weight percent based on total alloy weight, 5.5-6.5 aluminum, 1.7-2.1 tin, 1.7-2.1 molybdenum, 3.4-4.4 zirconium, 0.03-0.11 silicon, 0.1-0.4 germanium, titanium, and impurities.
[0035]
[0037] According to a third non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy includes, in weight percent based on total alloy weight, 5.9-6.0 aluminum, 1.9-2.0 tin, 1.8-1.9 molybdenum, 3.5-4.3 zirconium, 0.06-0.11 silicon, 0.1-0.4 germanium, titanium, and impurities.
[0036]
[0038] According to a fourth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy further comprises, in weight percent based on the total alloy weight, 0-0.30 oxygen, 0-0.30 iron, 0-0.05 nitrogen, 0-0.05 carbon, 0-0.015 hydrogen, and 0-0.1 each of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper.
[0037]
[0039] According to a fifth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the embodiments above, the titanium alloy includes zirconium-silicon-germanium intermetallic compound precipitates.
[0038]
[0040] According to a sixth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy has a hardness of 8×10 at a temperature of at least 476.7° C. (890° F.) under a load of 358.5 MPa (52 ksi). -4 (24 hours) -1 The steady creep rate is less than 100 MPa.
[0039]
[0041] According to a seventh non-limiting embodiment of the present disclosure, a method of producing a titanium alloy includes solution treating a titanium alloy at 1780°F to 1800°F for 4 hours, cooling the titanium alloy to ambient temperature at a rate dependent on a section thickness of the titanium alloy, aging the titanium alloy at 1025°F to 1125°F for 8 hours, and air cooling the titanium alloy, wherein the titanium alloy has a composition as detailed in each or any of the preceding embodiments.
[0040]
[0042] According to an eighth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy exhibits an ultimate tensile strength at 482.2°C (900°F) of at least 896.3 MPa (130 ksi).
[0041]
[0043] According to a ninth non-limiting aspect of the present disclosure, the present disclosure also provides a titanium alloy consisting essentially of, in weight percent based on total alloy weight, 5.5-6.5 aluminum, 1.5-2.5 tin, 1.3-2.3 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.1-2.0 germanium, titanium, and impurities.
[0042]
[0044] According to a tenth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the aluminum content of the alloy is 5.9 to 6.0, in weight percent based on the total alloy weight.
[0043]
[0045] According to an eleventh, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the tin content of the alloy is 1.7 to 2.1, in weight percent based on the total alloy weight.
[0044]
[0046] According to a twelfth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the tin content of the alloy is 1.9 to 2.0, in weight percent based on the total alloy weight.
[0045]
[0047] According to a thirteenth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the molybdenum content of the alloy is 1.7 to 2.1, in weight percent based on the total alloy weight.
[0046]
[0048] According to a fourteenth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the molybdenum content of the alloy is 1.8 to 1.9, in weight percent based on the total alloy weight.
[0047]
[0049] According to a fifteenth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the zirconium content of the alloy is 3.4 to 4.4, in weight percent based on the total alloy weight.
[0048]
[0050] According to a sixteenth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the zirconium content of the alloy is 3.5 to 4.3, in weight percent based on the total alloy weight.
[0049]
[0051] According to a seventeenth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the silicon content of the alloy is, in weight percent based on the total alloy weight, 0.03 to 0.11.
[0050]
[0052] According to an eighteenth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the silicon content of the alloy is 0.06 to 0.11, in weight percent based on the total alloy weight.
[0051]
[0053] According to a nineteenth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the germanium content of the alloy is 0.1 to 0.4 weight percent based on the total alloy weight.
[0052]
[0054] According to a twentieth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, in a titanium alloy, the oxygen content is 0 to 0.30, the iron content is 0 to 0.30, the nitrogen content is 0 to 0.05, the carbon content is 0 to 0.05, the hydrogen content is 0 to 0.015, and each of the contents of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper is 0 to 0.1, all in weight percent based on the total weight of the titanium alloy.
[0053]
[0055] According to a twenty-first non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, a method of producing a titanium alloy includes solution treating a titanium alloy at 1780°F to 1800°F for 4 hours, cooling the titanium alloy to ambient temperature at a rate dependent on a section thickness of the titanium alloy, aging the titanium alloy at 1025°F to 1125°F for 8 hours, and air cooling the titanium alloy, wherein the titanium alloy has a composition detailed in each or any of the foregoing embodiments.
[0054]
[0056] According to a twenty-second, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy has a hardness of 8×10 at a temperature of at least 476.7° C. (890° F.) under a load of 358.5 MPa (52 ksi). -4 (24 hours) -1 The steady creep rate is less than 100 MPa.
[0055]
[0057] According to a twenty-third, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the embodiments above, the titanium alloy exhibits an ultimate tensile strength at 482.2°C (900°F) of at least 896.3 MPa (130 ksi).
[0056]
[0058] According to a twenty-fourth non-limiting embodiment of the present disclosure, the present disclosure also provides a titanium alloy including, in weight percent based on total alloy weight, 2-7 aluminum, 0-5 tin, 0-5 molybdenum, 0.1-10.0 zirconium, 0.01-0.30 silicon, 0.05-2.0 germanium, 0-0.30 oxygen, 0-0.30 iron, 0-0.05 nitrogen, 0-0.05 carbon, 0-0.015 hydrogen, titanium, and impurities.
[0057]
[0059] According to a twenty-fifth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy has a hardness of 8×10 at a temperature of at least 476.7° C. (890° F.) under a load of 358.5 MPa (52 ksi). -4 (24 hours) -1 The steady creep rate is less than 100 MPa.
[0058]
[0060] According to a twenty-sixth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy further comprises 0-5 chromium, in weight percent based on the total alloy weight.
[0059]
[0061] According to a twenty-seventh, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy further comprises, by weight percent based on the total alloy weight, 0 to 6.0 of each of niobium, tungsten, vanadium, tantalum, manganese, nickel, hafnium, gallium, antimony, cobalt, and copper.
[0060]
[0062] According to a twenty-eighth non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy has a hardness of 8×10 at a temperature of at least 476.7° C. (890° F.) under a load of 358.5 MPa (52 ksi). -4 (24 hours) -1 The steady creep rate is less than 100 MPa.
[0061]
[0063] According to a twenty-ninth, non-limiting embodiment of the present disclosure, which may be used in combination with each or any of the above embodiments, the titanium alloy further comprises 0-5 chromium, in weight percent based on the total alloy weight.
[0062]
[0064] It should be understood that this specification presents aspects of the invention that are relevant for a clear understanding of the present invention. Certain aspects that are obvious to those skilled in the art and therefore do not aid in a better understanding of the present invention have not been presented in order to simplify the specification. Although only a limited number of embodiments of the present invention are necessarily described in this specification, those skilled in the art will recognize that many modifications and variations of the present invention can be used in light of this specification. All such modifications and variations of the present invention are intended to be included within the scope of this specification and the following claims. [Mode of the invention] [1] Weight percent based on total alloy weight: 5.5~6.5 Aluminum, 1.5 to 2.5 tin, Molybdenum 1.3~2.3 Zirconium, 0.1 to 10.0 Silicon, 0.01 to 0.30 0.1 to 2.0 germanium, Titanium, and Titanium alloy containing impurities. [2] Weight percent based on total alloy weight: 5.5~6.5 Aluminum, 1.7 to 2.1 tin, Molybdenum, 1.7 to 2.1 Zirconium, 3.4 to 4.4 Silicon, 0.03 to 0.11 0.1 to 0.4 germanium, Titanium, and 2. The titanium alloy of 1, containing impurities. [3] Weight percent based on total alloy weight: 5.9~6.0 Aluminum, 1.9~2.0 tin, Molybdenum 1.8~1.9 Zirconium, 3.5 to 4.3 Silicon, 0.06 to 0.11 0.1 to 0.4 germanium, Titanium, and 2. The titanium alloy of 1, containing impurities. [4] Weight percent based on total alloy weight: Oxygen from 0 to 0.30 Iron from 0 to 0.30; Nitrogen from 0 to 0.05 0 to 0.05 carbon, 0 to 0.015 hydrogen, and 2. The titanium alloy of claim 1, further comprising 0 to 0.1 of each of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper. [5] 2. The titanium alloy of 1, containing zirconium-silicon-germanium intermetallic compound precipitates. [6] The titanium alloy is characterized in that it can be subjected to a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7°C (890°F) and a strength of 8 x 10 -4 (24 hours) -1 2. A titanium alloy as described in claim 1, exhibiting a steady-state creep rate of less than 1000 K. [7] 1. A method for producing a titanium alloy, comprising: The titanium alloy is solution-treated at 971.1°C (1780°F) to 982.2°C (1800°F) for 4 hours. cooling the titanium alloy to ambient temperature at a rate dependent on the cross-sectional thickness of the titanium alloy; Aging the titanium alloy at 551.7°C (1025°F) to 607.2°C (1125°F) for 8 hours; and cooling the titanium alloy in air; 1. The method of claim 1, wherein the titanium alloy has a composition as set forth in claim 1. [8] 2. The titanium alloy of claim 1, wherein the titanium alloy exhibits an ultimate tensile strength at 482.2°C (900°F) of at least 896.3 MPa (130 ksi). [9] Weight percent based on total alloy weight: 5.5~6.5 Aluminum, 1.5 to 2.5 tin, Molybdenum 1.3~2.3 Zirconium, 0.1 to 10.0 Silicon, 0.01 to 0.30 0.1 to 2.0 germanium, Titanium, and An alloy of titanium consisting essentially of impurities.
[10] 10. The titanium alloy of claim 9, wherein the aluminum content of the alloy, in weight percent based on total alloy weight, is 5.9 to 6.0.
[11] 10. The titanium alloy of claim 9, wherein the tin content of the alloy, in weight percent based on total alloy weight, is 1.7 to 2.1.
[12] 10. The titanium alloy of claim 9, wherein the tin content of the alloy, in weight percent based on total alloy weight, is 1.9 to 2.0.
[13] 10. The titanium alloy of claim 9, wherein the molybdenum content of the alloy, in weight percent based on total alloy weight, is 1.7 to 2.1.
[14] 10. The titanium alloy of claim 9, wherein the molybdenum content of the alloy, in weight percent based on total alloy weight, is 1.8 to 1.9.
[15] 10. The titanium alloy of claim 9, wherein the zirconium content of the alloy, in weight percent based on total alloy weight, is 3.4 to 4.4.
[16] 10. The titanium alloy of claim 9, wherein the zirconium content of the alloy, in weight percent based on total alloy weight, is 3.5 to 4.3.
[17] 10. The titanium alloy of claim 9, wherein the silicon content of the alloy is, in weight percent based on total alloy weight, 0.03 to 0.11.
[18] 10. The titanium alloy of claim 9, wherein the silicon content of the alloy is, in weight percent based on total alloy weight, 0.06 to 0.11.
[19] 10. The titanium alloy of claim 9, wherein the germanium content of the alloy is 0.1-0.4, in weight percent based on total alloy weight.
[20] In the titanium alloy, The oxygen content is 0 to 0.30; The iron content is 0 to 0.30. The nitrogen content is 0 to 0.05. The carbon content is 0 to 0.05; The hydrogen content is 0 to 0.015; The content of each of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper is 0 to 0.1; 10. The titanium alloy of claim 9, wherein all weight percentages are based on the total weight of the titanium alloy. [twenty one] 1. A method for producing a titanium alloy, comprising: The titanium alloy is solution-treated at 971.1°C (1780°F) to 982.2°C (1800°F) for 4 hours. cooling the titanium alloy to ambient temperature at a rate dependent on the cross-sectional thickness of the titanium alloy; Aging the titanium alloy at 551.7°C (1025°F) to 607.2°C (1125°F) for 8 hours; and cooling the titanium alloy in air; 11. The method of claim 10, wherein the titanium alloy has a composition as set forth in claim 10. [twenty two] The titanium alloy is characterized in that it can be subjected to a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7°C (890°F) and a strength of 8 x 10 -4 (24 hours) -1 10. A titanium alloy as recited in claim 9, exhibiting a steady-state creep rate of less than 1000 MPa. [twenty three] 10. The titanium alloy of claim 9, wherein the titanium alloy exhibits an ultimate tensile strength at 482.2°C (900°F) of at least 896.3 MPa (130 ksi). [twenty four] Weight percent based on total alloy weight: 2~7 aluminum, 0 to 5 tin, Molybdenum from 0 to 5 Zirconium, 0.1 to 10.0 Silicon, 0.01 to 0.30 Germanium, 0.05 to 2.0 Oxygen from 0 to 0.30 Iron from 0 to 0.30; Nitrogen from 0 to 0.05 0 to 0.05 carbon, 0 to 0.015 hydrogen, Titanium, and Titanium alloy containing impurities. [twenty five] The titanium alloy is characterized in that it can be subjected to a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7°C (890°F) and a strength of 8 x 10 -4 (24 hours) -1 25. A titanium alloy as recited in claim 24, exhibiting a steady-state creep rate of less than 25.
[26] Weight percent based on total alloy weight: 25. The titanium alloy of claim 24, further comprising 0 to 5 chromium.
[27] Weight percent based on total alloy weight: 25. The titanium alloy of claim 24, further comprising 0.0 to 6.0 of each of niobium, tungsten, vanadium, tantalum, manganese, nickel, hafnium, gallium, antimony, cobalt, and copper.
[28] The titanium alloy is characterized in that it can be subjected to a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7°C (890°F) and a strength of 8 x 10 -4 (24 hours) -1 28. A titanium alloy as described in claim 27, exhibiting a steady-state creep rate of less than 200.
[29] Weight percent based on total alloy weight: 28. The titanium alloy of claim 27, further comprising 0 to 5 chromium.
Claims
1. Weight percent based on total alloy weight: Aluminum 5.5 to 6.5, 1.5 to 2.5 tin, 1.3 to 2.3 molybdenum, 0.1 to 10.0 zirconium, 0.01 to 0.30 silicon, 0.1 to 2.0 germanium, optionally, oxygen from 0 to 0.30; optionally, iron from 0 to 0.30; optionally, 0 to 0.05 nitrogen; optionally, 0 to 0.05 carbon; optionally, 0 to 0.015 hydrogen; optionally, 0 to 5 chromium; optionally, 0 to 0.1 each of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper; Titanium, and A titanium alloy comprising impurities, A titanium alloy containing intermetallic precipitates including zirconium, silicon and germanium.
2. Weight percent based on total alloy weight:
2. The titanium alloy of claim 1, wherein the tin content is from 1.7 to 2.1 weight percent, the molybdenum content is from 1.7 to 2.1 weight percent, the zirconium content is from 3.4 to 4.4 weight percent, the silicon content is from 0.03 to 0.11 weight percent, and the germanium content is from 0.1 to 0.4 weight percent.
3. Weight percent based on total alloy weight:
2. The titanium alloy of claim 1, wherein the aluminum content is 5.9 to 6.0 weight percent, the tin content is 1.9 to 2.0 weight percent, the molybdenum content is 1.8 to 1.9 weight percent, the zirconium content is 3.5 to 4.3 weight percent, the silicon content is 0.06 to 0.11 weight percent, and the germanium content is 0.1 to 0.4 weight percent.
4. The titanium alloy is subjected to a 8×10 strain test under a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7° C. (890° F.). -4 (24 hours) -1 2. The titanium alloy of claim 1, exhibiting a steady-state creep rate of less than
5. 10. The titanium alloy of claim 1, wherein the titanium alloy exhibits an ultimate tensile strength at 482.2°C (900°F) of at least 896.3 MPa (130 ksi).
6. Weight percent based on total alloy weight: Aluminum 5.5 to 6.5, 1.5 to 2.5 tin, 1.3 to 2.3 molybdenum, 0.1 to 10.0 zirconium, 0.01 to 0.30 silicon, 0.1 to 2.0 germanium, optionally, oxygen from 0 to 0.30; optionally, iron from 0 to 0.30; optionally, 0 to 0.05 nitrogen; optionally, 0 to 0.05 carbon; optionally, 0 to 0.015 hydrogen; optionally, 0 to 0.1 each of niobium, tungsten, hafnium, nickel, gallium, antimony, vanadium, tantalum, manganese, cobalt, and copper; Titanium, and A titanium alloy comprising impurities, A titanium alloy containing intermetallic precipitates including zirconium, silicon and germanium.
7. 7. The titanium alloy of claim 6, wherein the aluminum content of the alloy, in weight percent based on total alloy weight, is 5.9 to 6.
0.
8. 7. The titanium alloy of claim 6, wherein the tin content of the alloy is from 1.7 to 2.1, in weight percent based on total alloy weight.
9. 7. The titanium alloy of claim 6, wherein the tin content of the alloy is from 1.9 to 2.0, expressed as a weight percent based on total alloy weight.
10. 7. The titanium alloy of claim 6, wherein the molybdenum content of the alloy, in weight percent based on total alloy weight, is 1.7 to 2.
1.
11. 7. The titanium alloy of claim 6, wherein the molybdenum content of the alloy is, in weight percent based on total alloy weight, from 1.8 to 1.
9.
12. 7. The titanium alloy of claim 6, wherein the zirconium content of the alloy, in weight percent based on total alloy weight, is from 3.4 to 4.
4.
13. 7. The titanium alloy of claim 6, wherein the zirconium content of the alloy, in weight percent based on total alloy weight, is 3.5 to 4.
3.
14. 7. The titanium alloy of claim 6, wherein the silicon content of the alloy is, in weight percent based on total alloy weight, from 0.03 to 0.
11.
15. 7. The titanium alloy of claim 6, wherein the silicon content of the alloy is, in weight percent based on total alloy weight, from 0.06 to 0.
11.
16. 7. The titanium alloy of claim 6, wherein the germanium content of the alloy is 0.1 to 0.4 weight percent based on total alloy weight.
17. The titanium alloy is subjected to a 8×10 strain test under a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7° C. (890° F.). -4 (24 hours) -1 7. The titanium alloy of claim 6, exhibiting a steady-state creep rate of less than
18. 7. The titanium alloy of claim 6, wherein the titanium alloy exhibits an ultimate tensile strength at 482.2°C (900°F) of at least 896.3 MPa (130 ksi).
19. Weight percent based on total alloy weight: Aluminum from 2 to 7, optionally, 0 to 5 tin, optionally, 0 to 5 molybdenum; 0.1 to 10.0 zirconium, 0.01 to 0.30 silicon, Germanium, from 0.05 to 2.0 optionally, oxygen from 0 to 0.30; optionally, iron from 0 to 0.30; optionally, 0 to 0.05 nitrogen; optionally, 0 to 0.05 carbon; optionally, 0 to 0.015 hydrogen; optionally, 0 to 5 chromium; optionally, 0 to 6.0 each of niobium, tungsten, vanadium, tantalum, manganese, nickel, hafnium, gallium, antimony, cobalt, and copper; Titanium, and A titanium alloy comprising impurities, A titanium alloy comprising intermetallic precipitates including zirconium, silicon and germanium, and exhibiting a steady-state creep rate of less than 8×10 −4 (24 hr) −1 under a load of 358.5 MPa (52 ksi) at a temperature of at least 476.7° C. (890° F.).
Citation Information
Patent Citations
Method and article relating to high strength erosion resistant titanium alloy
JP2008190039A
Titanium-containing article and method for making
JP2011012340A
Process for preparation of near-alpha titanium alloys
US4309226A
